Dampak Penyesuaian Pekerjaan terhadap Kinerja Karyawan UMKM: Peran Keterlibatan Kerja sebagai Mediator pada IKM Logam Baja Kabupaten Tegal - Alfian Adi Saputra; Gita Lorenza; Imelda Cleo Oktavelina; Muhammad Khairul Ikhwan; Miftakhul Arsyi; Vita Putri Revana; Mei Rani Amalia (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to understand the relationship between job crafting and employee performance, while examining the role of work engagement as a mediator within small and medium metal industry enterprises (SMEs) in Tegal Regency. The research employed a quantitative approach, using questionnaires distributed to employees of the relevant SMEs to collect data. Data analysis was conducted using SPSS version 22 to examine the relationships among variables and the significance of their effects. The results indicate that job crafting has a negative and significant effect on employee performance, while simultaneously exerting a positive and significant influence on work engagement. These findings suggest that effective job crafting can enhance employee engagement, fostering motivation and active participation in work tasks, but does not directly improve overall employee performance. The practical implications of this study provide a reference for SME managers to design more adaptive human resource management strategies, enhance job satisfaction, and achieve sustainable long-term impact. Additionally, the research emphasizes the importance of understanding psychological and behavioral factors among employees to increase organizational effectiveness and productivity. This study contributes to both theoretical and practical insights regarding the strategic management of human capital in small and medium-scale industrial settings.